Faktor-Faktor yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil di Wilayah Puskesmas Kuta Baro Kabupaten Aceh Besar - Erliana Erliana; Cut Nurhasanah; Cut Sriyanti (PT. Intelek Cendikiawan Nusantara, 2026)
Anemia in pregnancy remains a significant public health problem worldwide and contributes to maternal and fetal morbidity and mortality. The World Health Organization (WHO) reported that approximately 40% of pregnant women globally experience anemia, with higher prevalence in developing countries. Several factors such as maternal age, parity, nutritional status, education level, and compliance with iron supplementation influence the occurrence of anemia during pregnancy. This study aimed to identify factors associated with anemia among pregnant women in the working area of Kuta Baro Community Health Center, Aceh Besar. This study used an observational analytical design with a cross-sectional approach. The population consisted of pregnant women who attended antenatal care services, with a total sample of 72 respondents selected using purposive sampling. Data were collected using structured questionnaires and maternal health records. Data were analyzed using Chi-Square test with a significance level of 0.05. The results showed that there were significant relationships between maternal knowledge (p = 0.004), compliance with iron tablet consumption (p = 0.001), and nutritional status (p = 0.012) with the incidence of anemia. Meanwhile, maternal age (p = 0.214) and parity (p = 0.187) were not significantly associated. In conclusion, knowledge, iron supplementation compliance, and nutritional status are important factors related to anemia in pregnancy. Strengthening health education and nutritional programs is essential to reduce the prevalence of anemia among pregnant women.